INTEGRATION OF PROBLEM-SOLVING AND ETHNOMATHEMATICS APPROACHES TO ENHANCE STUDENTS’ MATHEMATICAL REPRESENTATION ABILITY - Tesi Kumalasari; Amir Danis; Christian Sinaga (Jurnal Buah Hati, 2025)
Mathematical representation ability is one of the fundamental skills needed by students to understand concepts and solve mathematical problems. However, the results of the study indicate that this ability is still low in most elementary school students. This study aims to develop a mathematics learning tool based on the Problem Solving approach and integrated with Ethnomathematics to improve students' mathematical representation ability. The study used the Research and Development (R&D) method with the Plomp development model consisting of three phases, namely initial research, development, and assessment. The research subjects were 30 students. The research instruments included validation sheets, teacher assessment sheets, student response sheets, implementation observation sheets, and mathematical representation ability tests (pre-test and post-test). The results showed that the developed learning tool met practical criteria with an average LKPD readability of 4.60 (very good category) and learning implementation of 94.5% (very good category), and was effective with an increase in the average pre-test score of 56.20 to a post-test of 83.87 and a gain score of 0.63 (medium-high category). Thus, there was a significant increase in the average post-test results of students' mathematical representation abilities, namely 83.87 through Problem Solving and Ethnomathematics-based learning devices.